Influence between Body Mass Index and Blood Pressure With Results of Urine Protein Examination in Pregnant Women at Bangkalan Health Center - Eny Susanti; Zakkiyatus Zainiyah; Siti Rochimatul Lailiyah (Universitas STRADA Indonesia, 2024)
Background: Preeclampsia is an increase in blood pressure that occurs after the 20th week of gestation. Until now, the exact cause of preeclampsia is not known. During the second trimester of pregnancy the pressure in the renal veins (renal venous pressure) changes and increases. Increased renal venous pressure causes proteinuria, especially in the orthostatic position, which causes a slightly greater change in kidney size. Purpose: The aim of this study was The Relationship Between Body Mass Index And Blood Pressure With Results Of Urine Protein Examination In Pregnant Women At Bangkalan Health Center. Methods: Analytical Research Design with a cross sectional approach. Independent variable Body Mass Index and Blood Pressure, dependent variable results of urine protein examination. The sample of this study were 210 pregnant women who carried out Integrated ANC at the Bangkalan Health Center, the sampling technique used Simple random sampling. Secondary data collection by looking at medical record data, statistical tests using Rank Spearman. Results: Based on statistical tests using Rank-Spearman, the results showed ρ value (0.024) <α (0.05) indicating that there is a relationship between Body Mass Index and urine protein examination results. The results of the study ρ value (0.020) <α (0.05) there is a relationship between blood pressure and the results of urine protein examination. Conclusion: Detection of proteinuria is very important in the diagnosis and treatment of hypertension in pregnancy. Proteinuria is the last symptom to appear in patients with preeclampsia.